Pendidikan Karakter Berbasis Nilai-Nilai Budaya Pondok Pesantren - Septiana, Widya (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2022)
Character education in relation to the cultural values ​​that exist in Islamic boarding schools can be said as an effort to implement the behavior of the students towards the surrounding community, as aimed at investing in this in the future in carrying out life relations in the community. Efforts to apply various santri characters can use strategies and methods which will then be grown and developed according to the surrounding culture and adapted to changes in social conditions that occur in society. The method that will be used in this research is by using qualitative methods by using this type of research library research. The results obtained from this study are that students need to be taught about character education in instilling cultural values ​​that exist in Islamic boarding schools in accordance with the norms and habits that exist in society. Examples of values ​​that must be applied are piety, simplicity, honesty, sincerity, cooperation, example, kinship, and independence, as these can be used as provisions in dealing with problems in the current era of development. So that way it will manifest students who have a Muslim personality in accordance with Islamic guidance and are beneficial for all humans. Keywords: Character, Culture, Islamic Boarding School